Comparative Study of Ochratoxin A Exposure through the Intake of Cereal Products in Two Climatic Moroccan Regions - Ahmed Tabarani; Abdellah Zinedine; João Miguel Rocha; Moez Sanaa; El Hassane Abdennebi (Toxins, 2023)
The present study aims to compare ochratoxin A (OTA) exposure through the intake of three cereal derivative products (bread, pasta and semolina) in two different Moroccan climatic regions (littoral and continental). OTA weekly intakes from cereal products were calculated using a deterministic approach for each region. Results showed a statistically significant difference (p < 0.05) of OTA exposure between the two regions. Indeed, the median OTA exposure was estimated at 48.97 ng/kg b.w./week in the littoral region, while it was estimated at 6.36 ng/kg b.w./week in the continental region. The probabilistic approach showed that, due to uncertainties, the 95th percentile of weekly OTA exposure associated with the three cereal products ranged from 66.18 to 137.79 (95% CI) with a median of 97.44 ng/kg body weight (b.w.)/week. Compared to the threshold of 100 ng/kg b.w./week, 95% of the cumulative distributions predicted an exceedance frequency between 0.42 and 17.30% (95% CI), with an exceedance frequency median of 4.43%. Results showed that cereal derivatives constitute an important vector of OTA exposure and cause a significant exceedance of toxicological reference value among large consumers in the littoral region, which suggests the urgency of reconsidering the maximum regulatory limit (MRL) set for OTA (3 µg/kg) in cereal derivatives by Moroccan authorities.